2019
DOI: 10.1007/s12562-019-01308-0
|View full text |Cite|
|
Sign up to set email alerts
|

Geographical variation in spawning histories of age-1 Pacific saury Cololabis saira in the North Pacific Ocean during June and July

Abstract: We examine geographical differences in percentages of age-1 Pacific saury Cololabis saira with previous spawning experience collected from 143°E to 165°W during June and July of 2013 and 2014. Previous spawning experience of fish was determined using a new histological method involving Victoria blue (VB)-positive ovarian arterioles. We also compared the radius of the otolith annual ring (ROA), which indicates fish body size at the beginning of the breeding season, with the incidence of previous spawning experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Previous studies have suggested that month, body length, and SST could affect the spawning activity of Pacific saury (Fuji, Kurita, et al, 2021;Suyama et al, 2019). In addition, maturation states of Pacific saury might be influenced by their migration origin because individual growth rates varied in different locations (Suyama et al, 2019). In this study, GAMMs were applied to examine the effects of month, body length (i.e., KnL), origin (western and eastern groups), and SST on the probability of MOS state occurrence (P MOS )…”
Section: Statistical Analysis Of Maturation Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that month, body length, and SST could affect the spawning activity of Pacific saury (Fuji, Kurita, et al, 2021;Suyama et al, 2019). In addition, maturation states of Pacific saury might be influenced by their migration origin because individual growth rates varied in different locations (Suyama et al, 2019). In this study, GAMMs were applied to examine the effects of month, body length (i.e., KnL), origin (western and eastern groups), and SST on the probability of MOS state occurrence (P MOS )…”
Section: Statistical Analysis Of Maturation Statesmentioning
confidence: 99%
“…Previous studies have suggested that month, body length, and SST could affect the spawning activity of Pacific saury (Fuji, Kurita, et al, 2021;Suyama et al, 2019). In addition, maturation states of Pacific saury might be influenced by their migration origin because individual growth rates varied in different locations (Suyama et al, 2019).…”
Section: Statistical Analysis Of Maturation Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, differences in the prey environment, such as zooplankton community structure (Shiota et al., 2013) and the composition of subarctic copepod stages (Yamaguchi et al., 2013), differ between eastern and western areas. Pacific saury growth and first spawning age also differ between eastern and western areas (Suyama, Nakagami, Naya, & Ueno, 2012; Suyama et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to the image, the spawning period of autumn cohort centered in October, thus became age‐1 in the subsequent October; likewise, the spawning month of winter cohort and spring cohort centered in February and May, respectively, and became age‐1 in the subsequent February and May, respectively. Whereas the spawning period of age‐1 fish extends from autumn to spring, with an intensive spawning period in winter in the subtropical waters including the Kuroshio and Kuroshio Extension Currents (Figure 1), that of age‐0 fish is limited to winter, that is, all age‐1 fish and a part of age‐0 fish spawn (Fuji et al., 2019; Suyama et al., 2019; Watanabe & Lo, 1989).…”
Section: Introductionmentioning
confidence: 99%